Urban Sufism of the Kopiah Community in Jayapura - Muhammad Thohri; Prosmala Hadisaputra (Universitas Islam Negeri Mataram, 2022)
This article highlights two main issues. First, how is the typology of urban Sufism practiced by the Kopiah community in Jayapura city? Second, what is the strategy for strengthening Sufism among the Kopiah community in Jayapura? This qualitative case study research garnered the data from twofold sources: interviews, multimodal artifacts, such as films, images, and relevant library sources pertinent to the Kopiah community’s activities. The findings showed that the Kopiah community practice urban Sufism in the form of innovatively and contextually changing tazkiyyat al-nafs (purification of the self). Although the community is not linked formally to any Sufi sect, it, however, is influenced by the Alawiyah Sufi Order, based on the recited remembrance, adopting the Ratib al-Haddad. Tazkiyat al-nafs rituals adhere to a loud voice. It focuses on the study of the Qur’an and fiqh. It conducts Islamic teachings via dialogues entitled “Ngopi” (abbreviation of Ngobrol Perkara Iman or talking about faith) and “Ngobat” (abbreviation of Ngobrol Perkara Taubat or talking about repentance). This study paper helps map a preliminary understanding of the urban Sufism in eastern Indonesia, particularly in Jayapura.